Pendidikan Nilai Karakter dalam Tradisi Lisan Nyanyi Panjang Bujang Si Undang pada Masyarakat Suku Petalangan Provinsi Riau - Erni, Erni; Herwandi, Herwandi (GERAM: Gerakan Aktif Menulis, 2018)
One of the oral traditions of Pelalawan people loaded with character values ​​is the Long Chant of the Bujang Si Undang. In the long song Bujang Si Undang depicted portrait of ideal character of pelalawan people who can be guided as effort to maintain local wisdom of Petalangan society. This paper aims to describe the value of character education contained in the Legend of the Legal Bujang Si. Techniques performed in analyzing data using content analysis (content analysis). The result of the research shows that Singing Long Bujang Si Undang has educational content of character value. Educational values ​​of the characters contained in the Legend of Singles Long Leg there are five, namely the character of faith and cautious, honest, intelligent, resilient, and caring. Character education in Long Singing Sing song with the focus of faith and cautious reflected from the character of obedience to parents and mandate. The value of character education with honest focus is depicted from the honest character and responsibility. The education of the character's character with the focus of the intelligent character is depicted from the virtue character of demanding science and openness. Educational values ​​of characters with strong character focus are depicted from the character of hard work, diligent, and diligent, independent, confident, and courageous. Educational values ​​of characters with a focus of caring character depicted from sincere character, willing to sacrifice, affection, mutual cooperation, and spirit of unity.